2019
DOI: 10.3329/kyamcj.v10i2.42785
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical Outcomes Following Laparoscopic Vs. Open Mesh Repair of Inguinal Hernia 85

Abstract: Background: As a part of modern surgical procedure, laparoscopic mesh repair of inguinal hernia should be safe, effective and have a short period of convalescence. Objective: This study was designed to compare the outcome following inguinal hernia repair, performed by laparoscopic technique and open mesh Lichtenstein (tension-free) repair. Materials and Methods: This prospective quasi experimental study was carried out in the department of surgery, Bangabandhu Sheikh Mujib Medical University, for a period of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 5 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…20,22 The disadvantages of laparoscopic surgery include requirement of general anesthesia, longer operative time and learning curve and more expensive equipment. [22][23][24][25][26] The youngest patient in the present study was a 20 years old male and the oldest patient was 65 years old male with a mean of 52. 26 Also, the study of Singh et al, reported that mean age was 36.81 years and all patients were male.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…20,22 The disadvantages of laparoscopic surgery include requirement of general anesthesia, longer operative time and learning curve and more expensive equipment. [22][23][24][25][26] The youngest patient in the present study was a 20 years old male and the oldest patient was 65 years old male with a mean of 52. 26 Also, the study of Singh et al, reported that mean age was 36.81 years and all patients were male.…”
Section: Discussionmentioning
confidence: 67%
“…[22][23][24][25][26] The youngest patient in the present study was a 20 years old male and the oldest patient was 65 years old male with a mean of 52. 26 Also, the study of Singh et al, reported that mean age was 36.81 years and all patients were male. 27 Whereas Koshariya et al reported that the youngest patient in his study was a 32-year-old male and oldest patient was 79-year-old male with a mean age 57.12 in laparoscopic hernia repair and 57.00 in open inguinal hernia repair and with a very high incidence of inguinal hernia in males (94%).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations